2020
DOI: 10.3889/oamjms.2020.5295
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Pesticide Exposure and Neurological Signs and Symptoms in Farmers in Magelang District, Central Java, Indonesia

Abstract: BACKGROUND: Excessive use of pesticides is known to cause neurotoxicity. Chronic effects of pesticide poisoning include neuropathy and tremors. AIM: This study aimed to determine the association between pesticide exposure and the occurrence of neurological signs and symptoms, especially neuropathy and tremor, in farmers. METHODS: This was a cross-sectional study. The study location was Seloprojo Village, Ngablak District, Magelang Regency, Central Java Province. Farmers as subjects were recruited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This condition leads to an increase in the number of people specifically farmworkers and their families exposed to pesticides either during agricultural activities or at home even though proper personal protective equipment is worn (4). Some studies demonstrated a significant relationship between pesticide exposure and cancer risks (15)(16)(17), which include diseases persisting for a long time, such as insulin-dependent (6,(18)(19)(20), cardiac (21)(22), and neurological disorders (23)(24). Thyroid hormone disruption can cause organ disorders that are linked with many diseases (25).…”
Section: Cite This Asmentioning
confidence: 99%
“…This condition leads to an increase in the number of people specifically farmworkers and their families exposed to pesticides either during agricultural activities or at home even though proper personal protective equipment is worn (4). Some studies demonstrated a significant relationship between pesticide exposure and cancer risks (15)(16)(17), which include diseases persisting for a long time, such as insulin-dependent (6,(18)(19)(20), cardiac (21)(22), and neurological disorders (23)(24). Thyroid hormone disruption can cause organ disorders that are linked with many diseases (25).…”
Section: Cite This Asmentioning
confidence: 99%
“…3,4 A recent report from a study on farmers in Central Java, Indonesia, revealed that 68.3% of participants had cholinesterase levels below the reference value indicating exposure to acetylcholinesterase inhibitor pesticides, and neuropathic symptoms were found in 59.2% of participants. 5 Previous studies have elucidated the critical role of CYP450 (CYP) in the human bio metabolism of xenobiotic substances. Human CYP is known to have several essential effects regarding its role as a catalyst in phase 1 xenobiotic metabolism and clearance.…”
Section: Introductionmentioning
confidence: 99%